Bronchial Artery Embolization for Hemoptysis: A Retrospective Observational Study of 344 Patients - Hongxia Shao (Chinese Medical Journal, 2015)
Background: Hemoptysis is a significant clinical entity with high morbidity and potential mortality. Both medical management (in terms of resuscitation and bronchoscopic interventions) and surgery have severe limitations in these patients population. Bronchial artery embolization (BAE) represents the first-line treatment for hemoptysis. This article discusses clinical analysis, embolization approach, outcomes and complications of BAE for the treatment of hemoptysis. Methods: A retrospective analysis of 344 cases, who underwent bronchial arteriography at Tianjin Haihe Hospital between 2006 and 2013. Several aspects of outcome were analyzed: Demographics, clinical presentation, radiographic studies, results, complications and follow-up of BAE. Results: Three hundred and forty-four consecutive patients underwent bronchial arteriography, 336 of 344 patients (97.7%) performed BAE; there were 1530 coils for 920 arteries embolized; the main responsible sources for bleeding were right bronchial artery (29.7%), left bronchial artery (21.6%), combined right and left bronchial trunk (18.4%), right intercostal arteries (13.3%); 61 patients (17.7%) had recurrent hemoptysis within 1 month after undergoing BAE, 74 patients (21.5%) had recurrent hemoptysis over 1 month after undergoing BAE; The common complications of BAE included subintimal dissection, arterial perforation by a guide wire, fever, chest pain, dyspnea, etc. The follow-up was completed in 248 patients, 28 patients had been dead, 21 patients still bleed, 92 patients had lost to follow-up. Conclusions: The technique of BAE is a relatively safe and effective method for controlling hemoptysis . The complications of BAE are rare. Although the long-term outcome in some patients is not good, BAE may be the only life-saving treatment option in patients who are poor surgical candidates.